Convective drying of sweet pepper (Capsicum annuum L. ’Tres Cantos’) and yellow onion (Allium cepa L. ’Yellow Granex F1’) - Orozco, Joseph; Alonso, Juan; Gamero, Rafael; Picado, Apolinar (Nexo Revista Científica, 2023)
In this study, the drying kinetics of sweet pepper (Capsicum annuum L. 'Tres Cantos') and yellow onion (Allium cepa L. 'Yellow Granex F1') was experimentally investigated in a lab-scale tunnel dryer. The drying experiments were performed at three air temperatures (50, 60, and 70 °C) and three air velocities (1.0, 1.5, and 2.0 m/s). A volumetric shrinkage linear model from the literature was used to include the shrinkage effect on the drying process. From the drying curves, no constant rate period was observed. The drying process took place in a falling rate period. It was found that the changes in air velocity had essentially no effect on the drying process. In addition, a non-linear regression analysis was employed to determine the characteristic drying curve.